BUDAYA ORGANISASI DAN EFEKTIVITAS KOMUNIKASI ANTARPRIBADI SEBAGAI PREDIKTOR KOMITMEN TERHADAP ORGANISASI - Nancy Yusnita (Universitas Pakuan, 2020)
The research objective was to determine the factors related to commitment to the organization to increase Commitment to the Organization in the research on organizational culture factors and the effectiveness of interpersonal communication. The research was conducted on permanent employees of the Directorate of Human Resources and General Affairs, LPP RRI Headquarters, Jakarta, Indonesia. The research sample consisted of 66 permanent employees who were taken randomly from the population. This research mainly uses quantitative data (from questionnaires). Regression analysis is used to measure the influence between variables. The results showed that organizational culture had a positive and significant effect on organizational commitment. Likewise, interpersonal communication has a positive influence on commitment to the profession. Based on the results of this study, there are several recommendations to the Directorate of Human Resources and General Affairs of the LPP RRI Head Office, Jakarta to increase the commitment of employees of the organization.